1999
DOI: 10.1115/1.482784
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intrinsic Strain Softening on Strain Localization in Polycarbonate: Modeling and Experimental Validation

Abstract: Intrinsic strain softening appears to be the main cause for the occurrence of plastic localization phenomena in deformation of glassy polymers. This is supported by the homogeneous plastic deformation behavior that is observed in polycarbonate samples that have been mechanically pretreated to remove (saturate) the strain softening effect. In this study, some experimental results are presented and a numerical analysis is performed simulating the effect of mechanical conditioning by cyclic torsion on the subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
141
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(147 citation statements)
references
References 25 publications
6
141
0
Order By: Relevance
“…From numerical investigations it has become evident that the occurrence of plastic instabilities such as neck formation, but also crazing, is closely related to the intrinsic deformation behavior of polymer materials determined from constant true strain-rate compression experiments; [30][31][32] see Figure 2b. At relatively small deformations, the yield stress of the material is reached.…”
Section: Time-dependent Ductile Failure: Relation To Intrinsic Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…From numerical investigations it has become evident that the occurrence of plastic instabilities such as neck formation, but also crazing, is closely related to the intrinsic deformation behavior of polymer materials determined from constant true strain-rate compression experiments; [30][31][32] see Figure 2b. At relatively small deformations, the yield stress of the material is reached.…”
Section: Time-dependent Ductile Failure: Relation To Intrinsic Behaviormentioning
confidence: 99%
“…Initiation of the instability is triggered by strain softening, whereas strain hardening stabilizes the localization allowing it to grow. [29][30][31][32] Now we can of course also compare this intrinsic behavior in a constant true strain-rate compression test (Figure 2b), with that in a constant true-stress compression experiment, Figure 2a. Upon loading, the strain increases at a decreasing rate, reaching a constant creep rate.…”
Section: Time-dependent Ductile Failure: Relation To Intrinsic Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…14 The resulting elastoviscoplastic model, with two basic elementssa linear elastic spring and a 3-D Eyring dashpotswas further refined by Govaert et al 5 by adding pressure dependence and (phenomenological) softening based on the concept of Hasan et al, 15 and a neo-Hookean rubber spring representing strain hardening, as suggested by Tervoort and Govaert. 16 These models were among others used in the investigation of strain localization phenomena in polymers such as shear banding, necking, and crazing.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] These efforts were motivated by the desire to predict mechanical properties and performance and to develop (numerical) tools for better understanding and, finally, improving properties of homogeneous, as well as heterogeneous, polymer systems. 6 A landmark in this area of research is the original paper of Haward and Thackray from 1968, 1 where they proposed to govern the large strain deformation of polymers below their glass transition temperature by two separate processes.…”
Section: Introductionmentioning
confidence: 99%